Boron requirements of prunes: Diagnostic and treatment experiments in Sonoma County show promise in control of brushy branch disease of prune trees - C Hansen; E Proebsting; E Torpen (California Agriculture, 1958)
Symptoms of brushy branch declined and fruit yield increased following application of boron to injured prune trees in test plots near Windsor.